PROSPECTS FOR RELYING ON THE BASIS OF NATIONAL IDEOLOGY IN PROTECTING YOUNG PEOPLE FROM ALIEN AND HARMFUL IDEAS IN THE ERA OF MODERN GLOBALIZATION - Kuyliyev Tulkin; Kenjayeva Dilrabo Rominovna (Journals Park Publishing, 2024)
In this article, in the process of modern globalization, during the construction of a new Uzbekistan and the construction of a democratic society, attention to increasing the socio-political and social activity of youth has become an important direction of the policy of our state. As the younger generation grows up, in addition to processes in all types of educational institutions, issues such as increasing the importance of other forms of education, the formation and improvement of an active life position, and social activity among our youth also become important. great importance in increasing the effectiveness of ideological factors. The article also reveals the prospects for the implementation of such a task as the formation of a healthy worldview among young people through the formation of a culture of using the Internet. Protecting young people from harmful ideas is based on effective means of implementing in practice the socio-philosophical and educational-ethical criteria of the new standard of the national idea.
Keywords: globalization, Internet, development, society, idea, national idea, spirituality, culture, education, upbringing, ideology, ideological threats, information attacks, social activism.